The Impact of Work From Anywhere (WFA) on Employee Productivity: A Literature Review : Array - Pani Apriani; Shabilla Rossinda (JABI (Journal of Accounting and Business Issues), 2025)
This study aims to analyze the impact of Work From Anywhere (WFA) implementation on employee productivity through a systematic literature review using bibliometric analysis. The research employed a qualitative descriptive approach, utilizing secondary data from 1,146 journals collected through Publish or Perish from Scopus and Google Scholar databases. After systematic screening using Covidence following PRISMA guidelines, 67 relevant journals published between 2023-2025 were analyzed. The study utilized VOSviewer for bibliometric visualization to identify research clusters and keyword relationships. The findings reveal that flexibility emerges as the most dominant factor in enhancing employee productivity in WFA settings, including freedom to manage time, work location, and job priorities. Other productivity-enhancing factors include cost and time savings, improved work-life balance, work autonomy, quiet work environment, and organizational/technological support. Conversely, productivity decline is primarily caused by home distractions and social isolation. The bibliometric analysis identified four main research clusters: remote work structure and flexibility (red cluster), work model impact on performance (green cluster), human resource management and productivity (blue cluster), and pandemic impact on employee well-being (yellow cluster). The study provides strategic recommendations for organizations to optimize WFA implementation through technological infrastructure investment, time management training, balanced work policies, and comprehensive employee support systems.